Role of Exogenous Salicylic Acid and Benzoic Acid Applications to Vascular Streak Dieback Disease Attack on Cocoa Seedlings - Fakhrusy Zakariyya; Agung Wahyu Susilo; Teguh Iman Santoso; Hardian Susilo Addy; Sulistyani Pancaningtyas (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2018)
Currently, vascular streak dieback (VSD) attacks have widespread in areas ofthe center of cocoa (Theobroma cacaoL.) production, especially inSulawesi. Salicylic acid and benzoic acid are part of phenol compounds reportedlyacts as bioimmunoregulator in increasing of plant resistance to that pathogen. The objec-tiveof this research was to investigate effect of exogenous salicylic acid and benzoic acid applications to VSD disease attack on cocoa seedlings.  The research was conducted at Indonesian Coffee and Cocoa Research Institute,Jember, East Java.  This experiment designed using randomized completely block  design with three replications. The treatments included concentrations of salicylic  acid in 0.5 mMol, 1 mMol, 2 mMol; benzoic acid with concentration 0.5 mMol, 1 mMol,2 mMol; and control (water spray). Observations were based on the incidence and severity damage  of disease, plant height, stem diameter, number of leaves, stelate trichome, chlorophyll, width and length of stomatal apperture, and number of stomata. Exogenoussalicylic acid and benzoic acid as phytohormone can reduce disease insidence and severity of VSD. In conclusion, our results indicated that exogenous salicylic acid and benzoic promoted stomatal closure in cocoa leaf by decreasing width-stomatal closure. Salicylic and benzoic acid had no effect to plant height, stem  diameter, number of leaves, length of stomatal apperture, number of stomata, and number of stelate trichome.